2015
DOI: 10.1177/1479972315583049
|View full text |Cite
|
Sign up to set email alerts
|

Whole body vibration training in patients with COPD

Abstract: In recent years, several studies have shown that whole body vibration training (WBVT) may be a beneficial training mode in a variety of chronic diseases and conditions such as osteoporosis, fibromyalgia, multiple sclerosis, or chronic low back pain. However, a systematic review on the effects of WBVT in patients with chronic obstructive pulmonary disease (COPD) has not been performed yet. An extensive literature search was performed using various electronic databases (PubMed, Embase, LILACS, and PEDro). They w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 22 publications
(35 reference statements)
2
40
0
2
Order By: Relevance
“…In a recently published systematic review, our work group identified six studies (including 235 COPD patients) applying WBVT in different approaches and settings ( e.g. WBVT versus passive control group, WBVT on top of endurance and strength training, WBVT during acute exacerbation) [5]. It was concluded that WBVT seems to be superior in improving functional exercise capacity in comparison to conventional exercise strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published systematic review, our work group identified six studies (including 235 COPD patients) applying WBVT in different approaches and settings ( e.g. WBVT versus passive control group, WBVT on top of endurance and strength training, WBVT during acute exacerbation) [5]. It was concluded that WBVT seems to be superior in improving functional exercise capacity in comparison to conventional exercise strategies.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that WBVT seems to be superior in improving functional exercise capacity in comparison to conventional exercise strategies. The underlying mechanisms of these benefits remain unclear but it is improvements in the neuromuscular system in particular that are speculated to cause these gains in exercise performance [5]. …”
Section: Introductionmentioning
confidence: 99%
“…However, a recently published systematic review [10] has summarized that there seems to be a conclusive tendency that WBVT may be an effective and promising additional exercise method beyond traditional training regimes in patients with COPD to increase functional exercise capacity .…”
Section: Introductionmentioning
confidence: 99%
“…WBVT is an exercise modality inducing myoelectric stimulation by oscillatory vibrations to a subject standing on a vibrating platform (22). It is an efficacious mode of exercise training in patients with COPD that improves exercise capacity and lower limbs functional performance (23)(24)(25).…”
Section: Whole Body Vibration Training (Wbvt) In Long-term (>1 Year) mentioning
confidence: 99%